Structure design and control strategy of a new alkaline water electrolyzer based on heat exchange. (29th May 2019) - Shen, Xiaojun; Zhang, Xiaoyun; Lv, Hong; Li, Guojie; Lie, Tek‐Tjing
Summary: The overall energy conversion efficiency and the power regulation performance of the volatile renewable energy alkaline water electrolyzer (AWE) hydrogen production system need to be improved. Efficient use of heat in the electrolysis process and optimization of the control strategy are technically feasible. According to the concept of heat exchange utilization, this paper proposes a series parallel modular structure of AWE, which realizes heat exchange and utilization between modules. Based on the electrothermal characteristics of AWE and the power fluctuation characteristics of volatile energy, the function positioning and control strategy of the module are proposed. Theoretical analysis, together with a case study, has been conducted to show the overall efficiency and power regulation characteristics of the traditional AWE, the traditional combined AWE and the proposed new AWE under various working scenarios. Research study results show that the proposed new structure and control strategy can effectively improve the overall energy efficiency and static as well as dynamic power regulation characteristics of the electrolyzer, with the energy efficiency increased up to 16%. Although the static power range decreases slightly in some conditions, it always maintains the ability of wide range regulation. The findings can provide reference for the research and development of new AWE that improve the power response capability and the comprehensive utilization of energy under the premise of ensuring a certain power adjustment range. Abstract : Based on the electrothermal characteristics of the alkaline water electrolyzer (AWE), the internal parallel modular structure used to realize the exchange of heat energy between modules, improved the comprehensive energy conversion efficiency of the AWE; For wind power fluctuation characteristics, the module function division and control strategy is proposed to improve the dynamic power regulation characteristics of the AWE. Research results show that the proposed new structure and control strategy can effectively improve the overall energy efficiency and power regulation characteristics of the electrolyzer, with the energy efficiency increased up to 16%，which provide a reference for the research and development of new AWE for wind power consumption